SPE Symposium on Improved Oil Recovery 2008
DOI: 10.2118/113918-ms
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Value of Intelligent Well Technology against Reservoir Uncertainty

Abstract: Significant challenges remain in the development of optimized control techniques for intelligent wells, particularly with respect to properly incorporating the impact of reservoir uncertainty. Most optimization methods are model-based and are effective only if the model can be used to predict future reservoir behavior with no uncertainty. Recently developed schemes, which update models with data acquired during the optimization process, are computationally very expensive. We suggest that simple reactive contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…We investigate the predicted streamingpotential measurements resulting from production from a single horizontal well with multiple completions. This is a first step toward developing a feedback control strategy (Addiego-Guevara et al, 2008), which may be used to enhance production.…”
Section: Introductionmentioning
confidence: 99%
“…We investigate the predicted streamingpotential measurements resulting from production from a single horizontal well with multiple completions. This is a first step toward developing a feedback control strategy (Addiego-Guevara et al, 2008), which may be used to enhance production.…”
Section: Introductionmentioning
confidence: 99%
“…This would result in an increase of the efficiency of the control strategies and a reduction of the uncertainties of the dynamic reservoir models (Addiego-Guevara et al, 2008;Jansen et al, 2008). The typical range of detection in the order of 10 m is particularly suitable for bottom water-drive reservoirs with thin oil layer-or steam-assisted gravity drainage processes.…”
Section: Resultsmentioning
confidence: 99%
“…The source of inspiration was a conceptual model analyzed by Addiego-Guevara et al (2008): a thin sandstone reservoir containing interbedded, laterally discontinuous shale barriers that reduce the effective vertical permeability. The porosity and permeability distributions, shown in Figure 1a and b, were created using an in-house geostatistical modeling software based on principal component analysis; a large number of realizations of typical geological features were used to create the final image (Sarma et al, 2008).…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have combined geological and or economic uncertainty with different smart well completion configurations and several ICV control optimization strategies [van Essen et al 2010] [Grebenkin 2013] [Addiego-Guevara et al 2008] [Schiozer and da Silva 2009] [Sampaio et al 2009]. Although it has been recognized that the choice of an optimal well trajectory is crucial to maximize the economic value of a reservoir, no studies have been found on well trajectory optimization for smart wells.…”
Section: Introductionmentioning
confidence: 99%